Analysis of Work Safety Behavior Among Workers in the Development Project at PT Bahagia Selalu Bersinar Housing Aura Park in Pondok Bestari Indah, Langdungsari, Malang Regency, East Java - Fifi Damayanti; Kiki Frida Sulistyani; Hilarius Hudi Prayoga (Journal of Evrímata: Engineering and Physics, 2026)
The construction sector in Indonesia continues to show a high risk of work accidents, largely due to human behavioral factors that have the potential to cause accidents. This study aims to analyze the work safety behaviors implemented by workers on the Aura Park Housing development project by PT Bahagia Selalu Bersinar in Malang Regency, East Java. The main focus of the analysis is on the level of Compliance in the application of Personal Protective Equipment (PPE) as the main indicator of Attitude towards safety. The research approach applied is quantitative with data collection methods using surveys and direct observations in the field over a period of one month. Data on daily PPE use compliance were collected from 77 project workers. The research data shows that worker compliance with PPE use standards reaches a very low level, which is only 20%, far below the minimum standard of 60%. Gloves are the most frequently used PPE, while the use of other vital PPE such as helmets, safety shoes, and vests is still very minimal. This low level of compliance indicates that work safety behavior at the project site has not been optimally implemented and a safety culture has not been well established.